The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1519/1533-4287(2003)017<0580:ioiikp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Injury in Kickboxing Participation

Abstract: Cardio kickboxing classes have become a popular form of exercise to enhance fitness. This study surveyed kickboxing participants and instructors to ascertain the severity, type, and incidence of injuries sustained while performing cardio kickboxing exercise. The respondents consisted of 77.4% instructors and 29.3% participants with a mean age of 32.29 years (+/-8.98 years). Injury from kickboxing exercise was reported by 29.3% of the respondents, 31% of the instructors, and 15.5% of the participants. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
2
18
0
3
Order By: Relevance
“…This is in accordance with previous findings among fitness instructors. (du Toit & Smith, 2001;Romaine et al, 2003) As previous studies have described injuries on the vocal cords and hearing among instructors, (Rumbach, 2013;Wilsont & Herbstein, 2003) it was somewhat surprising that very few instructors reported injury in the head region. One explanation for this might be underreporting of such injuries, and that specific questionnaires are necessary to detect this problem.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is in accordance with previous findings among fitness instructors. (du Toit & Smith, 2001;Romaine et al, 2003) As previous studies have described injuries on the vocal cords and hearing among instructors, (Rumbach, 2013;Wilsont & Herbstein, 2003) it was somewhat surprising that very few instructors reported injury in the head region. One explanation for this might be underreporting of such injuries, and that specific questionnaires are necessary to detect this problem.…”
Section: Discussionmentioning
confidence: 98%
“…(Garrick et al, 1986) Another study presented prevalence numbers among aerobics instructors as high as 77% with the most frequent injury locations being leg, foot/ankle and knee. (du Toit & Smith, 2001) Romaine et al(2003) found that 31% of cardio kickboxing instructors had experienced injuries related to such classes, and reported back, knee, hip and shoulder as the most frequent injury locations. Among step aerobics instructors, 73.5% reported chronic lower extremity injuries, and among others working hours and instructor experience were factors explaining the injury prevalence (Malliou et al, 2014) Musculoskeletal pain is common among athletes (Foss, Holme, & Bahr, 2012;Jacobsson et al, 2012) and in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The latter authors also reported that Australian kickboxers sustained more head injuries than those from the United Kingdom and Holland (51.6% vs. 42.5%), but fewer lower extremity injuries (39.8% vs. 53.4%, respectively). Romaine et al [28] stated that the most common sites of injury for kickboxers were the back, the knee, and the ankle; the most common types of injuries were strains followed by sprains, and tendinitis. Professional fighters were 2.5 times more likely to get injured compared with amateurs (rate ratio, 2.51), while defeated fighters were 3.5 times more likely to get injured compared with winners (rate ratio, 3.48) [27].…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic point of view, limiting the number of kickboxing sessions per week may help to reduce injury rates [28], and the coach should adapt specific training/competition contests for young and children kickboxers (e.g., light contact kickboxing in both simulated and official combats) by avoiding a full-contact kickboxing competition.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with other martial arts, contusions are the most common type of injury in karate [2] and taekwondo [27]. Muscle strains are also common, not only in judo but also in kickboxing [34]. Muscle strains might be incurred due to repeated body collisions during attack and defence manoeuvers.…”
Section: Discussionmentioning
confidence: 99%